Intention to Apply: A Perspective of Jakarta’s Generation Z based on Employer Brand Attractiveness and Organizational Reputation - Agatha, Priscilla; Amanda Setiorini (PT FORMOSA CENDEKIA GLOBAL, 2024)
Generation Z is a digital native generation and is expected to dominate the workforce by 2025. In Jakarta, youth employment remains high and is dominated by Generation Z, highlighting the need for human resources to understand the generation’s behavioral tendencies and attract top talent. Quantitative research utilizing a self-administered questionnaire to 248 university students in 5 different universities in Jakarta is implemented. PLS-SEM data analysis method is used. All hypotheses are found significant with a positive influence. Social value of employer brand attractiveness and financial performance of organizational reputation are found to be the most attractive factor by Generation Z. The implications of this research can be used for developing an effective human resource strategy to attract Generation Z